FOREIGN LANGUAGE TEACHING IN SUDANESE UNIVERSITIES: GOALS, ATTITUDES, AND REALITY - Mugaddam, Abdel Rahim Hamid (Indonesian Journal of Applied Linguistics, 2012)
Abstract: The goals and means of language study continue in the very center of debates among specialists in language teaching/learning. Different views relating to language and its functions are reflected in two main approaches to language teaching/learning. On the one hand, language is considered to be principally instrumental, a means of communicating thought and information. One the other hand, language is viewed as an important element of human being’s thought processes, perceptions, and self-expressions; and as such, it is placed at the core of translingual and transcultural competence. This paper investigates the current situation of teaching/learning foreign languages in the Sudanese universities with special focus on the goals of teaching these languages and their role in students’ future. Goals of language teaching and students’ attitudes towards the process will be related to the job opportunities available for the students on graduation. Data for the paper have been collected using questionnaires and interviews administered to students and teachers from five language departments at Khartoum University: English, French, German, Russian, and Chinese. Questionnaires and interviews on language attitude will be administered among Four-year language majors representing the four departments. The central question the paper tries to answer is whether there is a realistic match between the goals of language teaching/learning set by policy makers and students’ interests and expectations. Results are expected to contribute to the efforts made to restructure language-in-education curriculum at university level in a way that addresses the expectations of both policy makers and students. Keywords: Foreign language teaching and learning, goals, attitude.